26 Poetas argentinos 1810-1920 - GHIANO, Juan Carlos (EUDEBA, 1960)
CONTENIDO : LOPEZ Y PLANES, Vicente; LUCA, E.de; HIDALGO, B.; VARELA, J.C.; ECHEVERRIA, E.; GUTIERREZ, J.M.; MARMOL, J.; ASCASUBI, H.; DEL CAMPO, E.; HERNANDEZ, J.,GUIDO Y SPANO, C.; GUTIERREZ, R.; ANDRADE, O.V.; OBLIGADO, R.; PALACIOS, P.B.; ALMAFUERTE; DIAZ, L.; LUGONES, L.; CARRIEGO, E.; BANCHS, E.; ROJAS, R.; ARRIETA, R.A.; MARASSO, A.; FERNANDEZ MORENO, B.; STORNI, Alfonsina; GUIRALDES, Ricardo